794. IRIS FURSEORUM. (September 2014) - Hall, Tony; Seisums, Arnis
Summary A new juno iris for the Flora of Afghanistan, Iris furseorum T. Hall & Seisums, is described and illustrated. It was collected in N.E. Afghanistan by Paul and Polly Furse in 1966 and has been maintained in cultivation.